2016
DOI: 10.1049/iet-nbt.2015.0039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of metal nanoparticles and their effects on seed germination and seedling growth in commercially importantEruca sativa

Abstract: The synthesis, characterisation and application of metal nanoparticles have become an important and attractive branch of nanotechnology. In current study, metallic nanoparticles of silver, copper, and gold were synthesised using environment friendly method (polyols process), and applied on medicinally important plant: Eruca sativa. Effects of application of these nanoparticles were evaluated on seed germination frequency and biochemical parameters of plant tissues. Seeds of E. sativa were germinated on Murashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 29 publications
5
32
1
Order By: Relevance
“…So we can conclude that CuNPs are responsible for inducing more stress as compared to AgNPs and AuNPs. Our observations are in line with Zaka et al (2016) who reported similar findings in an attempt to check the effect of MNPs for TPC and TFC in Eruca sativa.…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tfc)supporting
confidence: 93%
“…So we can conclude that CuNPs are responsible for inducing more stress as compared to AgNPs and AuNPs. Our observations are in line with Zaka et al (2016) who reported similar findings in an attempt to check the effect of MNPs for TPC and TFC in Eruca sativa.…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tfc)supporting
confidence: 93%
“…The TAC was found to be highest (4.66 mg GAE/g FW) at higher concentration of NPs (160ppm). The results were supported by Zaka et al 43 study where they have reported that the TAC was found to be 7µg Ascorbic acid/mg FW and DPPH 12% on Eurica sativa when exposed to Cu2O NPs.…”
Section: Effect On Antioxidant Propertiessupporting
confidence: 73%
“…Zinc oxide (ZnO) NPs as an inorganic micronutrient have a beneficial effect on plant growth, cell division, and structure and function of membrane because of their high electron mobility, large surface area, and catalytic activity . Most of the recent studies are focused on the effects of NPs on seed germination , plant growth rate physiological responses , and secondary metabolites production . Recent studies have shown that plant growth, development, and physiology are significantly affected by NPs; however, their role on plant secondary metabolism, especially regarding callus culture, is still obscure .…”
Section: Introductionmentioning
confidence: 99%